2021
DOI: 10.3389/fneur.2021.758536
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs for Rehabilitative Management in Common Health-Related Problems Negatively Impact the Quality of Life of Community-Dwelling Stroke Survivors

Abstract: Purpose: Community-dwelling stroke survivors have various unmet needs for rehabilitative management, but there is a lack of in-depth investigations on common health problems after stroke. Moreover, the association between unmet needs and health-related quality of life (HRQoL) has not been thoroughly investigated. This study aimed to investigate the unmet needs for rehabilitative management in common problems after stroke and their associations with HRQoL among community-dwelling stroke survivors.Methods: A fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Kim and colleagues found that the presence of one or more unmet needs for rehabilitative management in common health-related problems (i.e., spasticity, pain, anxiety/depression, etc.) are independent negative predictors of individuals’ quality of life [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim and colleagues found that the presence of one or more unmet needs for rehabilitative management in common health-related problems (i.e., spasticity, pain, anxiety/depression, etc.) are independent negative predictors of individuals’ quality of life [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For chronic stroke patients, researchers have made several attempts to assess the long-term disabilities and rehabilitative needs of the stroke patients ( 41 , 42 ). However, there is no standardized assessment method in long-term stroke survivors supported by NHI or LTCI.…”
Section: Transitional and Long-term Rehabilitation Care Systemmentioning
confidence: 99%
“…Approximately one in three patients reported unmet rehabilitation needs post-stroke (7). These needs can influence the patients’ health-related quality of life (7,8). A previous study showed that in community-dwelling stroke survivors, an increased number of unmet rehabilitation needs was significantly associated with a lower health-related quality of life (8).…”
Section: Introductionmentioning
confidence: 99%